Finasteride in androgenetic alopecia in men - Walkowiak, Hanna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2007)
Androgenetic alopecia in men occurs in the majority of men over 40 years old and is becoming a significant psychological problem. Androgens have profound effects on scalp and body hair in the human scalp. Testosterone acts in tissues after conversion into dihydrotestosterone. Miniaturization of the scalp hair follicles due to the androgens’ activity constitutes the process background. The alpha 5 reductase enzyme, a key mediator of male pattern loss participating in testosterone metabolism, plays a significant role in the disease aetiopathogenesis. Diagnosis of andogenetic alopecia was based on an interview and the clinical picture. The clinical picture is quite typical and consists of hair loss in the fronto-parietal area. The 8-step Hamilton-Norwood scale is used to evaluate the severity of the disease. The treatment of androgenetic alopecia is not always successful, but has psychological importance. Finasteride is one of the drugs inhibiting androgenetic alopecia in men. The best effects are seen when finasteride is administrated at a dose of 1 mg/day for 24 months. The drug is usually well tolerated and if any adverse events occur, in most cases they are not a reason to interrupt the treatment.